PENGEMBANGAN UMKM SEBAGAI DAYA TARIK WISATAWAN : (Studi Pada Desa Wisata Kampoeng Di Kalurahan Kampung Kapanewon Ngawen Kabupaten Gunungkidul) - Purnamasari, Martina Indah; Amira, Gibrina Rizki; Nugroho, Ricardho Dhaniel; Rosalia Widhiastuti (POPULIKA, 2024)
Tourism development can bring many benefits and benefits to both a village and its community.  It is hoped that this construction and development will be able to increase tourism, so that it can become a main sector in the development of community-managed businesses.  Tourism development efforts can create jobs for people who have potential in micro, small and medium enterprises or other businesses. The method used is a qualitative approach by collecting interview data, observation and documentation. Interviews were conducted with several informants, including tourism village managers, tourism village actors, community service providers and visitors.  In data analysis, researchers followed the flow of activities suggested by Miles and Huberman.  The flow of activities consists of data reduction, data presentation, and drawing conclusions which are carried out simultaneously.  The aim is to examine the potential of Kampoeng Tourism Village as an attractive tourism destination.  And the role of the community and village institutions can contribute to the development and preservation of MSMEs and create structures that can increase village tourism potential. Keywords: Development; Management; Tourist Village Kampoeng.